KOMUNIKASI PEMASARAN TAMAN SATWA TARU JURUG (TSTJ) SURAKARTA DALAM MENINGKATKAN WISATAWAN DI MASA PANDEMI - Nursaid, Fajar Rizki; Pratiwi, Rhesa Zuhriya Briyan; Husen, Fathurrohman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2022)
One of the tourism potentials of Surakarta City which is quite affected by the pandemic is the Taru Jurug Animal Park (TSTJ) Surakarta. Therefore, it is necessary to have a strategy in the implementation of communication and promotion from TSTJ Surakarta in order to continue to exist. The purpose of this study was to describe the marketing communication strategy of TSTJ Surakarta in order to increase tourists during the pandemic. This type of research is descriptive qualitative, with data collection through interviews, observation, and documentation. The results of the research show that the marketing communication strategy of TSTJ Surakarta is carried out with several criteria, including: implementing health protocols in tourist visits, socializing non-cash payments in the tourism process, optimizing education about flora and fauna through the use of the Instagram social media account @jurugsolozoo, and several supporting activities introduced in the TSTJ Surakarta tourist visit, such as: gowes tours, fun fishing, and animal care tickets. In addition, TSTJ Surakarta also provides merchandise as an effort to introduce tourism potential, as well as provide additional information about what is available at TSTJ Surakarta to tourists.